John Fiske's Semiotic Analysis of Moral Education in “Budi Pekerti” Film - Nur Afni Rachman (Journal of Language, Communication, and Tourism, 2023)
This study used qualitative research with John Fiske's semiotic approach. This research aimed to reveal the reality, representation, and ideology regarding moral education in the film by Wregas Bhanuteja entitled “Budi Pekerti”. The film had a high artistic aesthetic and was full of meaning. Film is an audio-visual media that combines both elements, namely narrative and cinematic. This study employed the semiotic method by John Fiske as the research method.  The signs shown in this film pointed to moral education which was currently a crisis in Indonesia. Reality, representation, and ideology regarding moral education were conveyed through conversations, choice of color tones, settings, soundtracks, and scenes. The results of the study showed that the film depicted current reality especially regarding the moral values in the society in Indonesia context. This also showed how current development of information and technology has strong correlation with people’s behavior especially related to moral values.